2019
DOI: 10.4028/www.scientific.net/msf.969.539
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Process Parameters Using Surface Response Methodology for Laser Welding of Titanium Alloy

Abstract: Laser beam welding input conditions are greatly influence the quality of the welded joints and they have significant role on the controlling of their strength and metallurgical properties. The metallurgical properties and weld bead geometry and mechanical properties of the joints determine the quality of the joints. In this study, the fusion zone width, penetration, width of the heat affected zone and strength of the titanium alloy welds were investigated using laser welding process. The surface response metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…With the expansion of application areas and increased market demand, the welding requirements for TC4 titanium alloy are growing. However, because of the high activity of titanium alloys, it is highly susceptible to oxidation during the welding process, forming a gas-rich layer, which can increase the welding difficulty [ 2 , 3 , 4 ]. Additionally, the welding of thick-walled titanium alloys is prone to problems such as porosity [ 5 ], cracking [ 6 ], deformation [ 7 , 8 ], and failure to meet performance requirements [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the expansion of application areas and increased market demand, the welding requirements for TC4 titanium alloy are growing. However, because of the high activity of titanium alloys, it is highly susceptible to oxidation during the welding process, forming a gas-rich layer, which can increase the welding difficulty [ 2 , 3 , 4 ]. Additionally, the welding of thick-walled titanium alloys is prone to problems such as porosity [ 5 ], cracking [ 6 ], deformation [ 7 , 8 ], and failure to meet performance requirements [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The bonded joints consist of the formation of precipitates, and the maximum shear strength is obtained at an operating temperature of 1135 °C. 19,20 Based on the consideration of hot cracking, precipitation, and heat input, the studies were found interesting based on GTAW welding results. GTAW welding was extensively investigated using continuous current and pulsed current.…”
Section: Introductionmentioning
confidence: 99%
“…The bonded joints consist of the formation of precipitates, and the maximum shear strength is obtained at an operating temperature of 1135 °C. 19,20…”
Section: Introductionmentioning
confidence: 99%
“…Response surface methodology (RSM) is a powerful mathematical tool used to optimize the process parameters in processes such as machining, welding, and casting etc [3][4][5] and also used to develop a mathematical model [6] and it minimize the number of experiments. Muralimohan Cheepu et al [7] developed a mathematical model and optimize the welding process parameters during the laser welding of titanium alloys and compared the obtained results from response surface methodology with experimental results. Shekhar Srivastava and R.K. Garg [8] developed a mathematical model and optimized GMA welding process parameters during the welding of IS2062 via RSM approach .…”
Section: Introductionmentioning
confidence: 99%